Diversity and Multigene Phylogeny of the Genus Floccularia (Agaricales, Basidiomycota) - Zai-Wei Ge; Hua Qu; Malka Saba; Tian Gao; Martin Ryberg (Journal of Fungi)
Floccularia is known as a northern-hemisphere-distributed genus with important economic values, especially in Western China. However, its species diversity in Asia and the phylogeny of this genus have not been critically studied. Based on worldwide sampling and multi-locus DNA sequence data (ITS, LSU, rpb2, tef1), the phylogeny of Floccularia was reconstructed, and the species diversity in Asia was critically studied on the basis of morphology and phylogeny. The results showed that five phylogenetic species can be recognized in this genus, of which there are four species in Asia, two species in North America and one species in Europe. According to our result, in addition to F. luteovirens, three new species, F. asiatica, F. flava and F. sinensis, were distributed in Asia, while in North America, F. pitkinensis and F. fusca could be synonyms of F. albolanaripes, as both species are phylogenetically intermingled within F. albolanaripes. Morphological descriptions of new species, color images of basidiomes, line drawings of their microscopic features, and a key to the Asian species of this genus are provided. Our study reconstructed the phylogeny of Floccularia for the first time and clarified the species diversity of Floccularia in Asia and suggests the need for detailed study of American specimens in order to accurately assess the diversity of Floccularia in America.